2018
DOI: 10.1684/epd.2018.0956
|View full text |Cite
|
Sign up to set email alerts
|

Early infancy‐onset stimulation‐induced myoclonic seizures in three siblings with inherited glycosylphosphatidylinositol (GPI) anchor deficiency

Abstract: Inherited glycosylphosphatidylinositol anchor deficiency causes a variety of clinical symptoms, including epilepsy, however, little information is available regarding seizures as a symptom. We report three siblings with inherited glycosylphosphatidylinositol anchor deficiency with PIGL gene mutations. The phenotypes of the subjects were not consistent with CHIME syndrome or Mabry syndrome, as reported in previous studies. All shared some clinical manifestations, including transient apnoea as neonates, dysmorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is noteworthy that PIGL gene variations are also associated with Mabry syndrome (characterized by hypotonia, seizures, intellectual disability, and increased blood levels of tissue nonspecific alkaline phosphatase), which is phenotypically distinct from CHIME syndrome. 3,[11][12][13] Our case illustrates phenotypic/genotypic variations in CHIME syndrome. Exome sequencing was particularly useful for diagnosis, widening the clinical spectrum of CHIME syndrome and enabling accurate genetic counseling.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is noteworthy that PIGL gene variations are also associated with Mabry syndrome (characterized by hypotonia, seizures, intellectual disability, and increased blood levels of tissue nonspecific alkaline phosphatase), which is phenotypically distinct from CHIME syndrome. 3,[11][12][13] Our case illustrates phenotypic/genotypic variations in CHIME syndrome. Exome sequencing was particularly useful for diagnosis, widening the clinical spectrum of CHIME syndrome and enabling accurate genetic counseling.…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, our patient's phenotype provides new data on the clinical spectrum of CHIME syndrome. It is noteworthy that PIGL gene variations are also associated with Mabry syndrome (characterized by hypotonia, seizures, intellectual disability, and increased blood levels of tissue nonspecific alkaline phosphatase), which is phenotypically distinct from CHIME syndrome 3,11–13 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the effectiveness of pyridoxine treatment for PIGV [7], PIGO [8], PIGS [9], and PGAP3 [10] deficiencies. However, pyridoxine unresponsiveness has been reported in patients with PIGA [13,26], PIGP [27], PIGL [19], PIGV [28], PIGO [29], PIGT [30], and PGAP2 [31] deficiencies. In the aforementioned patients, there was a heterogeneous treatment effect of pyridoxine even in patients with similar causative genes for IGDs.…”
Section: Discussionmentioning
confidence: 99%
“…All patients presented with decreased CD16 expression on blood granulocytes. Four patients were genetically diagnosed; among them, two exhibited PIGO deficiency [14], while two exhibited PIGL deficiency [19]. Whole-exome sequencing of the other patients revealed no pathogenic mutations, including in causative genes for pyridoxine-dependent epilepsy, including ALDH7A1, ALDH4A1, PLPBP, PNPO, and ALPL.…”
Section: Patientsmentioning
confidence: 97%
“…Apart from patients with focal onset there was also one with unknown onset of seizures. Other symptoms identified in presented GPIBD5 included intellectual (5/5) and motor (4/5) development delay, cerebellar atrophy (3/5), nystagmus, and strabismus (1/5; in the same subject) (46)(47)(48).…”
Section: Pigl (Phosphatidylinositol Glycan Anchor Biosynthesismentioning
confidence: 99%